PELINDUNGAN HUKUM DAN PEMENUHAN HAK TERHADAP PEKERJA PEREMPUAN: Studi Swalayan Indomaret Kecamatan Somba Opu Kabupaten Gowa - Agusti, Regina Elsya; Samin, Sabri; Hisbullah, Hisbullah (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
Legal protection of the rights of women workers is the fulfillment of basic rights inherent and protected by the constitution, this is regulated in Law Number 13 of 2003 concerning Manpower which includes protection for women workers who are entitled to be accepted and must be provided by employers. This study aims to determine the legal protection provided and received by female workers in Indomaret Swalayan, Somba Opu District, Gowa Regency. This research is a field research conducted with a juridical approach, data collection methods in the form of primary data and secondary data obtained through observations, interviews, documentation, collected data are analyzed qualitatively. The results of the study are that legal protection for women workers in accordance with the mandate of Law Number 13 of 2003 has not been fully implemented because there are still unfulfilled rights of women workers, such as payment of overtime and leave wages, provision of menstrual leave, and shuttle services for female workers who work after 23.00. The fulfillment of rights should be an integral part of legal protection efforts, and should be the domain of supervision from the government.